Re-modelling of venous thrombosis. (March 2013) - Malgor, R D; Labropoulos, N
Venous thromboembolism is one of the most common causes of morbidity and mortality in modern societies. The entirety of events involved in venous thrombus formation and resolution remains to be elucidated. Temporal relation between the initial cellular insult, thrombus formation and resolution is critical for instituting a prompt treatment. This paper analyses the current basic knowledge and the events involved in venous remodelling after an episode of venous thrombosis.